Divertor armour issues: lifetime, safety and influence on ITER performance - Pestchanyi, S. (Вопросы атомной науки и техники, 2009)
Comprehensive simulations of the ITER divertor armour vaporization and brittle destruction under ELMs of different sizes have revealed that the erosion rate of CFC armour is intolerable for an industrial reactor, but it can be considerably reduced by the armour fibre structure optimization. The ITER core contamination with carbon is tolerable for medium size ELMs, but large type I ELM can run the confinement into the disruption. Erosion of tungsten, an alternative armour material, under ELMs influence is satisfactory, but the danger of the core plasma contamination with tungsten is still not enough understood and potentially it could be very dangerous. Vaporization of tungsten, its cracking and dust production during ELMs are rather urgent issues to be investigated for proper choice of the divertor armour material for ITER. However, the erosion rate under action of the disruptive heat loads is tolerable for both armour materials assuming few hundred disruptions falls out during ITER lifetime. Комплексне дослідження процесів випарування та розтріскування теплозахисту дивертора під впливом ELM в ІТЕРі виявило, що швидкість ерозії теплозахисту з CFC неприйнятно велика для промислового реактора, але вона може бути значно зменшена завдяки оптимізації структури ниток CFC. Забруднення ядра ІТЕРа вуглецем є некритичним для ELMів середньої енергії, але великий ELM типу І може призвести до зриву розряду. Швидкість ерозії вольфраму, який є альтернативним матеріалом для теплозахисту, прийнятно мала, але небезпека забруднення розряду вольфрамом ще недостатньо вивчена, а потенційно це забруднення дуже небезпечно. Оцінка випарування вольфраму, його розтріскування та пилоутворення під час ELM – це питання, які потребують термінового рішення для правильного вибору матеріалу теплозахисту дивертора ІТЕРа. Однак ерозія обох матеріалів під впливом зривів цілком прийнятна, якщо припустити, що під час життя ІТЕРа відбудеться декілька сотень зривів. Комплексное исследование процессов испарения и растрескивания теплозащиты дивертора под действием ELM в ИТЕРе выявило, что скорость эрозии теплозащиты из CFC неприемлемо велика для промышленного реактора, но она может быть значительно уменьшена при оптимизации струтуры нитей CFC. Загрязнение ядра ИТЕРа углеродом некритично для ELMов средней энергии, но большой ELM типа I может вызвать срыв разряда. Скорость эрозии вольфрама, являющегося альтернативным материалом для теплозащиты, приемлемо мала, но опасность загрязнения разряда вольфрамом ещё недостаточно изучена, а потенциально это загрязнение очень опасно. Оценка испарения вольфрама, его растрескивания и пылеобразования во время ELM – это вопросы, требующие срочного решения для правильного выбора материала теплозащиты дивертора ИТЕРа. Однако эрозия обоих материалов под действием срывов вполне приемлема, если предположить, что в течение жизни ИТЕРа произойдёт несколько сот срывов.